2020
DOI: 10.15252/embr.202050264
|View full text |Cite
|
Sign up to set email alerts
|

Extended synaptotagmin regulates membrane contact site structure and lipid transfer function in vivo

Abstract: Inter‐organelle communication between closely apposed membranes is proposed at membrane contact sites (MCS). However, the regulation of MCS structure and their functional relevance in vivo remain debated. The extended synaptotagmins (Esyt) are evolutionarily conserved proteins proposed to function at MCS. However, loss of all three Esyts in yeast or mammals shows minimal phenotypes questioning the functional importance of Esyt. We report that in Drosophila photoreceptors, MCS number is regulated by PLCβ activi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 40 publications
6
30
0
Order By: Relevance
“…In accordance with this role, Sac1 and E-Syt2 were shown to co-localise while E-Syt2 knockdown significantly reduced Sac1 puncta at MCSs coinciding with accumulation of PI4P and PIP 2 ( Dickson et al, 2016 ). A role of E-Syt2 in PM PI regulation fits well with the observation that E-Syts regulates growth as shown in Drosophila ( Nath et al, 2020 ) and mammalian neurons ( Gallo et al, 2020 ) because of the role of PIP 2 in PM dynamics ( Scholze et al, 2018 ). Furthermore, E-Syts were found to interact with FGFR1 ( Tremblay et al, 2015 ), a receptor that regulates PM PIP 2 ( Herdman and Moss, 2016 ).…”
Section: Er-pm Contact Sites In Neuronssupporting
confidence: 84%
See 1 more Smart Citation
“…In accordance with this role, Sac1 and E-Syt2 were shown to co-localise while E-Syt2 knockdown significantly reduced Sac1 puncta at MCSs coinciding with accumulation of PI4P and PIP 2 ( Dickson et al, 2016 ). A role of E-Syt2 in PM PI regulation fits well with the observation that E-Syts regulates growth as shown in Drosophila ( Nath et al, 2020 ) and mammalian neurons ( Gallo et al, 2020 ) because of the role of PIP 2 in PM dynamics ( Scholze et al, 2018 ). Furthermore, E-Syts were found to interact with FGFR1 ( Tremblay et al, 2015 ), a receptor that regulates PM PIP 2 ( Herdman and Moss, 2016 ).…”
Section: Er-pm Contact Sites In Neuronssupporting
confidence: 84%
“…Additionally, hetero- or homodimerisation of SMP domains forms a hydrophobic channel that can facilitate lipid transfer in vitro ( Schauder et al, 2014 ; Yu et al, 2016 ) ( Figures 1 , 2 ). Finally, the single E-Syt orthologue in Drosophila , catalysing lipid transfer in photoreceptors at the submicrovillar cisternae and the growth of the organism ( Nath et al, 2020 ), was also suggested to modulate synaptogenesis ( Kikuma et al, 2017 ). E-Syts have since been identified in mammalian neuronal cells but, while it is plausible that they can perform these functions ( Giordano et al, 2013 ; Fernández-Busnadiego et al, 2015 ) their physiological significance in neurons is so far unclear and may only be noticeable under specific conditions.…”
Section: Er-pm Contact Sites In Neuronsmentioning
confidence: 99%
“…However, E-Syts and tricalbins do have physiological effects. For example, E-Syts can maintain PM lipid homeostasis, promote nerve transmission and synaptic growth, modulate virus-induced membrane fusion, mediate the endocytosis of FGFR, and play roles in insulin secretion and diet-induced obesity development (Saheki et al, 2016 ; Tremblay et al, 2016 ; Kikuma et al, 2017 ; El Kasmi et al, 2018 ; Xie et al, 2019 ; Nath et al, 2020 ; Zhang et al, 2020 ). Tricalbins act in maintaining PM integrity (Toulmay and Prinz, 2012 ; Collado et al, 2019 ).…”
Section: Lipid Exchanges At Er-pm Contact Sitesmentioning
confidence: 99%
“…Intriguingly, none of the strains tested showed significant changes in steady-state levels of any PI species ( Figure S2B ). Previous studies have implicated E-Syt family members in recycling diacylglycerol (DAG) from the PM to the ER and in the transfer of PI from the ER to the PM during the phosphoinositide cycle (Chang et al, 2013; Saheki et al, 2016; Nath et al, 2020). However, whilst PI homeostasis and PI4P synthesis at the PM apparently do not require the Tcb proteins, conversion of PI4P to PI(4,5)P 2 at the PM is impaired.…”
Section: Resultsmentioning
confidence: 99%